Women’s empowerment in agriculture: What role for food security in Bangladesh? - Sraboni, Esha; Malapit, Hazel J.; Quisumbing, Agnes R.; Ahmed, Akhter (International Food Policy Research Institute, 2013)
Using nationally representative survey data from Bangladesh, we examine the relationship between women’s empowerment in agriculture and two measures of household food security: per adult equivalent calorie availability and dietary diversity. We use the Women’s Empowerment in Agriculture Index to assess the extent of women’s empowerment in agriculture and instrumental variables techniques to correct for the potential endogeneity of empowerment. We find that the overall women’s empowerment score, the number of groups in which women actively participate, women’s control of assets, and a narrowing gap in empowerment between men and women within households are positively associated with calorie availability and dietary diversity.